Isobavachalcone Activates Antitumor Immunity on Orthotopic Pancreatic Cancer Model: A Screening and Validation - Liu, Xuanming; Zhang, Hongbo; Cao, Jianlin; Zhuo, Yuzhen; Jin, Jiahui; Gao, Qiaoying; Yuan, Xiangfei; Yang, Lei; Li, Dihua; Wang, Yan (Frontiers in Pharmacology, 2022)
Pancreatic cancer is accompanied by poor prognosis and accounts for a significant number of deaths every year. Since Psoralea corylifolia L. (PCL) possesses a broad spectrum of bioactivities, it is commonly used in traditional Chinese medicine. The study explored potential antitumor agents of PCL and underlying mechanisms in vitro and vivo. Based on network pharmacology, bioinformatics, and molecular docking, we considered isobavachalcone (IBC) as a valuable compound. The activity and potential mechanisms of IBC were investigated by RT-qPCR, immunohistochemistry, immunofluorescence, and flow cytometry. It was confirmed that IBC could inhibit Panc 02 cell proliferation and induce apoptosis via increasing the production of reactive oxygen species. IBC could attenuate the weight of solid tumors, increase CD8+ T cells, and reduce M2 macrophages in the tumor tissue and spleen. Another promising finding was that IBC alleviated the proportion of myeloid-derived suppressor cells (MDSCs) in the tumor tissue but had no change in the spleen. The study of pharmacological effects of IBC was carried out and suggested IBC restrained M2-like polarization of RAW 264.7 cells by inhibiting the expression of ARG1 and MRC1 and suppressed the expression of ARG1 and TGF-β in bone marrow-derived MDSC. In summary, this research screened IBC as an antineoplastic agent, which could attenuate the growth of pancreatic cancer via activating the immune activity and inducing cell apoptosis. It might be a reference for the antitumor ability of IBC and the treatment of the tumor microenvironment in pancreatic cancer.